(untitled) - IRRI (Manila, 1998)
This book represents the outcome of such a workshop on allelopathy in rice, held at IRRI in Novem. 1996, where scientists from around the world working on rice allelopathy gathered to discuss their research. This book could therefore be seen as the state of the art in rice allelopathy research. It will provide guidelines for further research in this area, which could give Asian farmers a tood for sustainable weed management.
Chiến lược quản lý cỏ dại
Keywords: rice - diseases and pests